The Serra de Santana in the semi-arid northeast: geographical aspects and possibility of sustainable practices - Lucena, Clara Yasmim De Souza Lucena (2022)
Wet enclaves that appear on the tops of mountains and plateaus are extremely important for the semi- arid region, as they are considered refuges for species of flora and fauna, as well as sources of water moisture for various human activities, since they have a cooler and wetter climate resulting from of the effects of altitude. In this context, the main objective of this research was to carry out a survey of the geographic aspects of Serra de Santana, with emphasis on climatic, pedological (i. e. soil), water and vegetation cover characteristics. It was also considered the uses of the land and the reflection on the possibilities of sustainable practices for the conservation of this important unit of the landscape that, despite having privileged geographical conditions in the semiarid region, as a “mild” climate in terms of thermal conditions , type of soil developed and hydrographic conditions of advantage, the process of use and occupation of the soil resulted in significant losses of native vegetation